2009
DOI: 10.1111/j.1440-0960.2009.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric vulval lichen sclerosus

Abstract: Lichen sclerosus (LS) in children is uncommon; however, it is an important differential diagnosis in any pre-pubertal child presenting with chronic vulval symptoms. The long-term prognosis is unknown; however, recent data suggests that the assumption that the condition will resolve at puberty may be incorrect. Children with LS require long-term management with topical corticosteroids, which remains the treatment of choice, as well as long-term follow up. We review the current literature on paediatric vulval LS. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
(75 reference statements)
2
16
0
6
Order By: Relevance
“…In a study including 327 patients, 60% were postmenopausal, and the mean age at diagnosis was 60; however, women in their reproductive age as well as girls may be affected . Lichen sclerosus is also seen in prepubertal girls in about 15% of cases; In our study, we found 88 (64.7%) patients with this condition, being that eight (9%) were prepubescent, 60 (68.1%) were postmenopause, and 20 (22.7%) were in their reproductive age. The disease extends beyond the vulvar region to involve the anogenital region in a figure‐of‐eight pattern in 85% to 90% of patients, with extragenital lesions noted in up to 15% .…”
Section: Discussionmentioning
confidence: 41%
“…In a study including 327 patients, 60% were postmenopausal, and the mean age at diagnosis was 60; however, women in their reproductive age as well as girls may be affected . Lichen sclerosus is also seen in prepubertal girls in about 15% of cases; In our study, we found 88 (64.7%) patients with this condition, being that eight (9%) were prepubescent, 60 (68.1%) were postmenopause, and 20 (22.7%) were in their reproductive age. The disease extends beyond the vulvar region to involve the anogenital region in a figure‐of‐eight pattern in 85% to 90% of patients, with extragenital lesions noted in up to 15% .…”
Section: Discussionmentioning
confidence: 41%
“…Lichen sclerosus (LS) is a type of a chronic inflammatory dermatitis; 5% to 15% of cases of LS occur in prepubertal girls . The estimated prevalence in girls is 1 in 900 .…”
mentioning
confidence: 99%
“…Bu tür hastaların dermatoloji kliniklerine yönlendirilmesi doğru tanı konulması açısından önem taşımaktadır (7). Ayırıcı tanıya giren diğer hastalıklar arasında oksiüriyazis, psöriasis, kontakt dermatit ve morfea gibi hastalıklar yer alır (4). Bu hastalıklarla ayırıcı tanısı dikkatli bir fizik muayene ve biyopsi gibi yöntemlerle yapılabilir.…”
Section: Sayın Editörunclassified
“…Çocukluk döneminde ergen kızlarda 1/900, erkek çocuklarda 1/200 oranında bildirilmiştir. Anogenital bölge tutulumu %85-98 arasında değişir (3,4). Klinik olarak, genital bölgede eritemli makül ve papüler olarak başlar.…”
unclassified